2022
DOI: 10.1002/ps.7236
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing identifies an ovary‐enriched microRNA, miR‐311‐3p, involved in ovarian development and fecundity by targeting EndophilinB1 in Bactrocera dorsalis

Abstract: Background The oriental fruit fly, Bactrocera dorsalis, is a highly invasive pest in East Asia and the Pacific. With the development of pesticides resistance, environment‐friendly pesticides are urgently needed. MicroRNAs (miRNAs) are critical regulators of numerous biological processes, including reproduction. Thus, it is significant to identify reproductive‐related miRNAs in this notorious pest to facilitate its control, such as RNAi‐based biopesticides targeting essential miRNAs. Results A high‐throughput s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In our previous study, we identified a series of miRNAs differentially expressed during sexual maturation and potentially involved in female reproduction from different periods of the ovary and fat body using small RNA sequencing [ 40 ]. After quantitative real-time PCR (qRT-PCR) verification and preliminary functional screening based on literature, we focused specifically on miR-2b-2-5p, whose function is still unknown in insect.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we identified a series of miRNAs differentially expressed during sexual maturation and potentially involved in female reproduction from different periods of the ovary and fat body using small RNA sequencing [ 40 ]. After quantitative real-time PCR (qRT-PCR) verification and preliminary functional screening based on literature, we focused specifically on miR-2b-2-5p, whose function is still unknown in insect.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, miRNAs play a critical role in regulating B. dorsalis female reproduction through post-transcriptional regulation of target genes. Several miRNAs involved in the regulation of vitellogenin synthesis, oocyte maturation, and egg production have been identified [110,111]. The molecular mechanisms underlying the female maturation process in B. dorsalis have been studied.…”
Section: Reproductive Biologymentioning
confidence: 99%
“…However, there have been many studies to explore functions of miRNAs in the insect. MiR-125-3p and miR-276b-3p target orb2 to regulate spermatogenesis of Bactrocera dorsalis [ 23 ], whereas miR-311-3p and miR-309a are involved in ovarian development [ 24 , 25 ]. In A. aegypti , miR-275, miR-305 [ 26 ] and miR-2940/Clumsy are responsible for egg development [ 27 ].…”
Section: Introductionmentioning
confidence: 99%